Challenges and opportunities in the use of transcriptomic characterization of human iPSC-derived BBB models. (October 2022) - Wellens, Sara; Gosselet, Fabien; Culot, Maxime
Abstract: The blood-brain barrier (BBB) is localized at the brain microvascular endothelial cells. These cells form a tight barrier, limiting the access of cells, pathogens, chemicals, and toxins to the brain due to tight junctions and efflux transporters. As the BBB plays a role in the assessment of neurotoxicity and brain uptake of drugs, human in vitro BBB models are highly needed. They allow to evaluate if compounds could reach the central nervous system across the BBB or can compromise its barrier function. Past decade, multiple induced pluripotent stem cell (iPSC)-derived BBB differentiation protocols emerged. These protocols can be divided in two groups, the one-step protocols, direct differentiation from iPSC to BBB cells, or the two-step protocols, differentiation for iPSC to endothelial (progenitor) cells and further induction of BBB characteristics. While the one-step differentiation protocols display good barrier properties, reports question their endothelial nature and maturation status. Therefore protocol characterization remains important. With transcriptomics becoming cheaper, this may support iPSC-derived model characterization. Because of the constraints in obtaining human brain tissue, good human reference data is scarce and would bear inter-individual variability. Additionally, comparison across studies might be challenging due to variations in sample preparation and analysis. Hopefully, increasing use of transcriptomics will allow in-depth characterization of the current iPSC-BBB models and guide researchers to generate more relevant human BBB models. Highlights: Modelling of the blood-brain barrier (BBB) BBB models from human pluripotent stem cells Challenges of iPSC-derived BBB models Use of transcriptomics for iPSC-derived BBB model characterization